(untitled) (Journal of the College of Basic Education, 2022)
International organizations concerned with food and agriculture have paid great attention to the issue of rural land uses, especially agricultural land uses, which constitute the main pattern in rural land uses, due to the effective role played by these uses in providing foodstuffs (plant and animal) to meet the requirements of the population, which is constantly increasing in all countries. around the world .In view of this importance, the geographer has taken it upon himself to contribute to the study of the geographical factors affecting the uses of the land and work to adapt them according to the requirements of any type of uses by analyzing the extent of their influence and the spatial variation of the uses of the land in order to reach the best use in the future.